Development of A Method for Transmitting and Encoding Technical Information About the State of a Mobile Robot Based on Least Significant Bit - Chala, O.; Yevsieiev, V.; Maksymova, S.; Ahmad Alkhalaileh (My University, 2024)
The rapid development of Industry 5.0 emphasizes the need for effective communication between humans and robotic systems, particularly mobile robots operating in dynamic environments. Traditional data transmission methods face challenges related to latency, security, and adaptability, necessitating new approaches to ensure seamless information exchange. This paper presents a method for encoding and transmitting technical information about a mobile robot's state using computer vision, enhancing reliability and autonomy. The proposed approach reduces dependence on network infrastructure, increases data transmission efficiency, and ensures robustness under varying environmental conditions. The findings contribute to the advancement of smart manufacturing by integrating vision-based communication into industrial robotics.
Keywords: Mobile Robot; Computer Vision; Data Encoding; Smart Manufacturing